2020
DOI: 10.1590/1981-6723.06919
|View full text |Cite
|
Sign up to set email alerts
|

Geração de resíduos na aquisição de vegetais in natura e minimamente processados por serviço de nutrição e dietética de um hospital público

Abstract: Este é um artigo publicado em acesso aberto (Open Access) sob a licença Creative Commons Attribution, que permite uso, distribuição e reprodução em qualquer meio, sem restrições desde que o trabalho original seja corretamente citado.Braz. J. Food Technol., Campinas, v. 23, e2019069, 2020 | https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Regarding fruits, the results of this study are similar to those found by Melo and Strasburg (2020), which was conducted in another public hospital, also in Porto Alegre. The inputs used were also similar in relation to the frequency of use in the monthly menus.…”
Section: Generation Of Wastesupporting
confidence: 89%
See 1 more Smart Citation
“…Regarding fruits, the results of this study are similar to those found by Melo and Strasburg (2020), which was conducted in another public hospital, also in Porto Alegre. The inputs used were also similar in relation to the frequency of use in the monthly menus.…”
Section: Generation Of Wastesupporting
confidence: 89%
“…The inputs used were also similar in relation to the frequency of use in the monthly menus. Besides that, the authors identified that if the hospital were to buy all vegetables items fresh, 25.6% more raw materials would be needed per year (Melo & Strasburg, 2020). Menezes et al, (2020) observed in their work that there was an increase of 246.2% in the acquisition of MPV in restaurants of a public university in a period of five years.…”
Section: Generation Of Wastementioning
confidence: 99%
“…In turn, vegetables are part of the preparation of menus in dish such as salads and side dishes 31 .…”
Section: Diet Patternsmentioning
confidence: 99%
“…For producers, minimal processing results in an increase in the product value and a reduction in losses during transport and storage. Moreover, by-products from minimal processing can be reused in the preparation of other foods, crop fertilization, and animal feed [16,[28][29][30].…”
Section: Market Of Mpvs In Brazilmentioning
confidence: 99%